The Application of Story Telling in Pre – School Children Towards Language Ability - Mamik Ratnawati; Monika Sawitri Prihatini; Heni Maryati; Ririn Probowati; Fitri Firranda Nurmalisyah; Edy Siswantoro (STRADA : Jurnal Ilmiah Kesehatan, 2020)
The development of children under five is very important part. Various forms of disease, malnutrition, lack of and love stimulation at this age will lead a negative impact that persists until adulthood even to old age. The purpose of this study is to determine the differences in language skills of children with the treatment of story telling methods without story telling. The method this study used quasy experiment with pre test – post test design of treatment and control group. A sample of 50 children in the Nusantara and Kasih Bunda play ground in Sudimoro Village, Megaluh, Jombang. Sampling was carried out using a simple ramdom sampling. The results of study found that treatment group had an influence of story telling on language skills in pre-school children, whereas there were no differences in story telling of language skills in the treatment and control groups.